Synthesis of different glutathione–sulfur mustard adducts of verified and potential biomarkers. Issue 42 (29th June 2018) - Bielmann, Andreas; Sambiagio, Nicolas; Wehr, Nathalie; Gerber-Lemaire, Sandrine; Bochet, Christian G.; Curty, Christophe
Abstract : Recently, several adducts between the chemical agent sulfur mustard (SM) and glutathione (GSH) were observed in vitro . We report the synthesis of different observed and potential GSH–SM bioadducts as reference materials for analytical investigation. Abstract : Sulfur Mustard (SM) is a blistering agent used as a chemical weapon. Glutathione (GSH) is involved in the β-lyase degradation pathway of SM and recently, bioadducts between SM and GSH were observed in vitro . While these bioadducts have never been isolated from in vivo tests or real poisoning with SM, they could be of interest as potential future biomarkers for the retrospective validation of exposure. We herein report the synthesis of different observed and new potential GSH–SM bioadducts as reference materials for analytical investigation. Two distinct approaches were investigated: a building-block pathway and the direct reaction with GSH. The availability of these references will aid future studies and may lead to the discovery of new GSH–SM biomarkers.